Matrix Ranking of the Technological Interventions Perceived by Farmers under IVLP - Anuj Kumar,; Ram Chand,; R.M. Fulzele,; Randhir Singh, (Journal of Agricultural Extension Management, 2025)
Indian agriculture supports about 65 per cent of its total population and contributes about 22 per cent to GDP. It is the mainstay of India's rural economy and contributes significantly towards employment and income generation. It is realized that 213 rd of the technologies do not percolate to the actual beneficiaries as they are developed without taking into consideration their socio-economic and psychological status. Since independence, several technologies have evolved for increasing the production, productivity of the crop as well as animals by improving the adoption behaviour of the farmers (Dwivedi et al., 2004)